592 Objective vs. Subjective Sleep Data in Early Childhood: Implications for Health Disparities Research. (3rd May 2021) - Cicalese, Olivia; Williamson, Ariel; Mindell, Jodi; Meltzer, Lisa
Abstract: Introduction: Given limited psychometric research with families of lower socioeconomic status (SES) and/or non-White backgrounds, this study explored the feasibility of and discrepancies between actigraphy and maternal-reported nightly child sleep in preschoolers of lower-SES and primarily Black backgrounds. Methods: Twenty-seven children (Mage=3.3 years, SD = 1.2 years; 59.3% girls; 85.2% Black; 100% family income <125% of the US poverty level) were asked to wear an actigraph for 14 days while mothers completed telephone-based sleep diaries. Bedtime, wake time, nighttime sleep duration, nap duration, and 24-hour sleep duration were collected by both measures. Paired t-tests examined actigraphic versus mother-reported child sleep. Results: Twenty-six percent of dyads (n=7) were excluded due to insufficient data (1-hour difference between measures on >50% of nights). There were no significant demographic differences between dyads with and without discrepant data. Diary-derived sleep onset was calculated by adding caregiver-reported bedtime and caregiver-reported sleep onset latency. There was no significant difference between actigraphy-derived sleep onset (M=10:20PM, SD=69min) and diary-derived sleep onset (M=9:59PM, SD=51min). Average actigraphy sleep offset (M=7:27 AM, SD=62 min) was 42 minutes earlier than diary-derived wake time (M=8:09 AM, SD=84 min), p<.05. Actigraphy-estimated nighttime (M=8.38 hours, SD=.80) and 24-hour sleep duration (M=9.31 hours, SD=1.13) were 0.92 and 0.85 hours shorter, respectively, than diary-derived nighttime (M=9.30 hours, SD=1.07) and total sleep duration (M=10.16 hours, SD=1.17), p<.005. There were no significant differences in average nap duration. The primary mother-reported barrier in completing diaries was limited awareness of child sleep due to work schedules. Conclusion: Study results highlight some of the challenges of collecting and scoring actigraphy and diary data in preschoolers of lower-income backgrounds, in particular missing diary data and discrepancies between actigraphy and diaries. These findings suggest a need to incorporate both subjective parental report and objective measurement of child sleep in clinical and research contexts, as well determine ways to enhance feasibility and scoring procedures. Support (if any): K23HD094905 (AAW)